(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
Employee motivation at the workplace is one of the main determinants of the workers’ productivity, as well as enticing organizational culture, which in turns affects the organizational performance. The usual approach to motivation is based on the concept of the carrot and the stick, which uses the reward and the punishment as the main tools for shaping the behaviour of employees. On the other hand, selfdetermination theory is based on the assumption that the employees are motivated when they believe that they are the agents of their own future. This paper investigates employee motivation at the workplace, using the case study of one Slovenian company. The survey covers a wide range of employees divided by gender, age, education and length of employment. The goal is to explore the level of motivation of the employees and discuss it within the context of self-determination theory and human resource development using the survey of employees in a Slovenian company. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.